Alone before the God: Gender, Status, and Nefertiti’s Image - Williamson, Jacquelyn.
Two architectural elements from Akhenaten’s early buildings at Karnak temple, a gateway and a set of pillars, are decorated with scenes of Nefertiti worshipping the Aten alone with only her daughters in attendance. Assumed to be examples of Nefertiti acting independently in the Aten cult, these monuments are sometimes hailed as precursors to the Sunshade of Re/sun temple structures so popular at Tell el-Amarna, most of which are associated with Akhenaten’s female family members. In this article these monuments are studied in the context of scenes reconstructed from Kom el-Nana, a Sunshade of Re at Tell el-Amarna, and other examples of women shown as the sole ritualist before a deity. It is proposed that images of Nefertiti acting alone are an indication of her lower status in the early part of Akhenaten’s reign, and that her status was elevated after the erection of the gateway and pillars. Nefertiti did not yet have enough status to act along side Akhenaten before year 6, and the gateway and pillars from Karnak cannot be considered precursors of Sunshade of Re temples, or as evidence for her independence in the Aten cult. In conclusion it is suggested that conversations about ancient women in religious hierarchies should be shifted from discussions about agency and power to discussions about importance, as a means to avoid the anachronistic application of western feminist thought to ancient evidence.